The Impact of Pornography Exposure on Adolescent Dating Behavior: In-sights from Beringin Jaya Village, Singing Hilir District, Kuantan Singingi Hilir Regency - Ratnasari, Ratnasari; Hulu, Rizman (Institute for Law and Economics Studies, 2022)
This research investigates the intricate influence of pornography on the dating behavior of adolescents within the cultural context of Beringin Jaya Village, situated in the Singing Hilir District, Kuantan Singingi Hilir Regency, Indonesia. Employing a mixed-methods approach, both quantitative and qualitative methodologies were utilized to explore the perceptions, attitudes, and behaviors of adolescents regarding pornography exposure and its impact on their dating dynamics. The study revealed a significant prevalence of pornography exposure among adolescents, correlating with altered perceptions of relationships, communication patterns, and nuanced understandings of consent. It highlighted the delicate balance between preserving traditional cultural values and navigating the challenges posed by modern influences. Findings emphasized the urgency for culturally sensitive interventions, community-based initiatives, and comprehensive sex education programs tailored to address the specific challenges posed by pornography exposure. This research serves as a beacon for understanding the complexities of adolescent development within a culturally specific context, offering insights that extend beyond Beringin Jaya Village, guiding future interventions, and fostering healthy relationship dynamics among adolescents